Analysis of User Requirements in the Development of Teacher Administration Applications : Case Report Vocational High School of PGRI 1 Sukabumi - Setiyani, Lila; Azis Somadulloh; Arif Maulana Yusuf (International Journal of Contemporary Studies in Education, 2023)
The online-based teacher administration system is expected to overcome problems in filling out teacher administration. At present, regulatory arrangements are still carried out physically, so educators spend most of their time working on these matters. Therefore, a superior administration system is needed. The purpose of this research is to make it easier for educators to manage administration online. In the process of making this system, researchers used the Linear Sequential Model method or commonly called the waterfall which is able to display accurate and useful information in assisting the development of this software. The results of this study are a website-based teacher administration system application that functions to make the work of educators much faster and the data stored in this application is much safer than manual administration.